2013
DOI: 10.1080/09585192.2013.792862
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cultural dimensions on Chinese expatriates' career capital

Abstract: The existing expatriation literature confirms that international assignments (IAs) are an essential tool for developing international talent and global managers. However, the majority of relevant studies are conducted in Western developed contexts and neglect the effects on individuals from emerging countries such as China. In the Chinese multinational companies context, this paper explores the concept of career capital comprising knowing-how, knowing-whom and knowing-why. Using Hofstede's cultural dimensions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…During the review process, I found some articles which could be categorised as being positioned in the transition zones of two paradigms. One example of positivist and interpretive analysis, which is not mixed methods, is that of Yao (2014), who applied exploratory and interpretive approaches in her qualitative studies. She searched for emerging themes, while using the flagship positivist research of Hofstede’s dimensions as analytical frames.…”
Section: Results: Paradigms In International Human Resource Managementmentioning
confidence: 99%
“…During the review process, I found some articles which could be categorised as being positioned in the transition zones of two paradigms. One example of positivist and interpretive analysis, which is not mixed methods, is that of Yao (2014), who applied exploratory and interpretive approaches in her qualitative studies. She searched for emerging themes, while using the flagship positivist research of Hofstede’s dimensions as analytical frames.…”
Section: Results: Paradigms In International Human Resource Managementmentioning
confidence: 99%
“…Given the breadth of the concept, it is no surprise that the boundaryless career paradigm is one of the most prevalent theoretical approaches in expatriation research (Shaffer et al, 2012(Shaffer et al, , p. 1288Andresen, Biemann & Pattie, 2015). The IC concept is built on boundaryless career ideas (Cerdin & Bird, 2008;Haslberger & Brewster, 2009) and often used in expatriation research (Yao, 2014;Jokinen, 2010;Jokinen et al, 2008). The intelligent career (IC) concept is well suited for the exploration of modern global careers (Suutari & Mäkelä, 2007).…”
Section: Modern Careersmentioning
confidence: 99%
“…For the Chinese worker, this translates into a high level of commitment to their organisation (Yang et al, 2012), avoidance of confrontation, respect for authority and an acceptance of unequal distribution of power (Chen et al, 2014). These attributes migrate with the worker into the new work environment and have significant implications for how Chinese migrants interact with others in the workplace (Yao, 2014).…”
mentioning
confidence: 99%